2015
DOI: 10.1089/acm.2014.0235
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Application of Silicone Wafers Containing Carbon Microcoils: Efficacy in Relieving Chronic Muscle Tension and Pain

Abstract: The use of Helical microcoils was found to be safe and efficacious in relieving muscle tension and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…Prior clinical trial study reported a significant decrease in pain VAS scores three weeks after the patches treatment. 10 In the current study, we measured pain scores at two time points: 2 and 4 weeks after the beginning of the treatment. We notice that relief of the symptoms occurred in six subjects (86%), on treatment day 15 (p 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior clinical trial study reported a significant decrease in pain VAS scores three weeks after the patches treatment. 10 In the current study, we measured pain scores at two time points: 2 and 4 weeks after the beginning of the treatment. We notice that relief of the symptoms occurred in six subjects (86%), on treatment day 15 (p 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The use of nanotechnology stands out among newer thermotherapy-based techniques developed for the treatment of neck pain. 10 Nanotechnology could be used for the treatment of neck pain by fixing to the skin small rounds silicone patches containing double spiral carbon nanotubes arranged in the form of a coil (Helical, Miyasaka Rubber Co., Chino, Nagano, Japan). These patches are designed for home use, made of an inert material, do not contain any type of drugs, and can be purchased without a medical prescription.…”
Section: Introductionmentioning
confidence: 99%
“…The emitted heat raises the local temperature by 0.7–1.2 °C. 10 , 11 It is documented that the local metabolic rate increases by 10%–13% as a consequence of each Celsius degree elevation. 12 The increase in metabolic function provides better nutrient supply, reduction of the inflammatory process, and elimination of toxins, resulting in muscle relaxation, pain relief, and localized stiffness alleviation.…”
Section: Introductionmentioning
confidence: 99%
“…Houve melhora na autopercepção da dor em 19 deles. Os principais efeitos colaterais descritos foram o prurido e eritema locais em 25% dos casos (Tsuji;Awade;Posso, 2015).…”
Section: Energia Térmicaunclassified
“…Os nanotubos são capazes de restaurar a circulação sanguínea em pontos gatilhos e reverter o processo de contração localizada, uma vez que a circulação comprometida no local tende a intensificar o processo inflamatório e gerar um círculo vicioso. Sua efetividade no combate à tensão muscular cervical já está documentada em literatura nacional (Tsuji;Awade;Posso, 2015). O tratamento com os NTC é um procedimento Nosso interesse é estudar de forma mais detalhada a atuação dos NTC no alívio da cervicalgia e da tontura.…”
Section: Introductionunclassified